The Effectiveness of Investigative Audit: Role of Whistleblowing System in Disclosing Fraud in Yogyakarta, Indonesia - Putri, Resha Monica; Purwati, Atiek Sri; Ramadhanti, Wita; Restianto, Yanuar E. (Badan Pemeriksa Keuangan Republik Indonesia, 2022)
This study aims to analyze the whistleblowing system’s effect on fraud disclosure with the effectiveness of investigative audits as a mediator. Data collection was conducted by distributing questionnaires to the functional employee of Yogyakarta’s Inspectorate comprising auditors and Government Affairs Supervision in the Regions (Pengawas Penyelenggaraan Urusan Pemerintahan di Daerah, P2UPD). Data analysis was conducted using WarpPLS, with research results proving that the whistleblowing system significantly impacts fraud disclosure and the effectiveness of investigative audits. Furthermore, it will prove that the effectiveness of investigative audits significantly affects fraud disclosure and mediates the whistleblowing system’s effect on fraud disclosure. The result implies that optimizing the supporting factors in the whistleblowing system and the investigative audit examination process can improve fraud disclosure in Yogyakarta.